2016
DOI: 10.1007/s40685-016-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Chief human resources officers on top management teams: an empirical analysis of contingency, institutional, and homophily antecedents

Abstract: Having the director of human resources (HR) as a member of the top management team (TMT) and giving him/her the title of chief human resources officer (CHRO) indicates an important strategic and symbolic choice. Such decisions not only determine who participates in controlling an organization and setting its strategic direction, but also reflect the organizational structure. In this paper, we examine the antecedents of CHRO presence according to the contingency, institutional, and homophily theories. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 116 publications
1
9
0
Order By: Relevance
“…Contingency theory helps researchers to understand the contingency factors that can influence L&D roles in organisations and it has been widely adopted in the HRM literatures to understand influence of contextual factors (Abt and zu Knyphausen-Aufseß, 2017), the dynamics of HRM roles (Caldwell, 2003; Farndale et al , 2010) in organisations and the antecedent of effectiveness of HR. Kast and Rosenzweig (1973) proposed that:…”
Section: Theoretical and Empirical Background To Researchmentioning
confidence: 99%
“…Contingency theory helps researchers to understand the contingency factors that can influence L&D roles in organisations and it has been widely adopted in the HRM literatures to understand influence of contextual factors (Abt and zu Knyphausen-Aufseß, 2017), the dynamics of HRM roles (Caldwell, 2003; Farndale et al , 2010) in organisations and the antecedent of effectiveness of HR. Kast and Rosenzweig (1973) proposed that:…”
Section: Theoretical and Empirical Background To Researchmentioning
confidence: 99%
“…Previous researchers have investigated the influence of factors such as age, gender, race, education, ethnicity and values on the forms and/or structures of social network relationships (Abt and Knyphausen-Aufseß, 2017; Badar et al , 2016; Badar et al , 2013; Barnes et al , 2017; Gallivan and Ahuja, 2015; McPherson et al , 2001). The present study found that homophily collaborations (between female and female or male and male authors) occurred less frequently than heterophilic collaborations (between male and female authors) (Badar et al , 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, the CHRO role is even sometimes considered a stepping stone towards the Chief Executive Officer (CEO) position (Poba-Nzaou et al 2020). Despite these developments and even though human capital remains a top challenge for most firms, research offers few insights into the strategic role of CHROs (Abt and Knyphausen-Aufseß 2017;Poba-Nzaou et al 2020).…”
Section: Introductionmentioning
confidence: 99%